Analysis and Mitigated of Total Harmonic Distortion from Solar Panel into Smart Grid - Muhamad Diah, Muhammad Abol Hassan; Saiman, Suhaimi (Evolution in Electrical and Electronic Engineering, 2022)
The advantage of this boost converter using after MPPT is to step-up an input voltage to some higher level as required by a load and the inverter is to convert DC to 3 phase AC source. The objective of this research was to simulate the power electronic circuit in a smart grid using MATLAB/Simulink software. Also, this research wants to analyze the harmonic distortion that can directly cause a smart grid. The result of this research showed the data of harmonic distortion before a smart grid. Also, the comparison results without using harmonic filter and harmonic filter are also shown in this paper.